Milk Production in Dairy Buffalo and the Development of “Dali Ni Horbo” as a Nutrient-Rich Local Food for the Batak Toba Community - Syafran Arrazy; Khairunnisa Khairunnisa; Putra Apriadi Siregar; Diva Nada Rizki Nuzlan; Rani Suraya (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Dali Ni Horbo, a traditional buffalo milk-based product from the Batak Toba community in North Sumatra, represents a culturally significant and nutritionally rich food. Despite its heritage value, its traditional form limits its appeal and market potential. This study aims to develop dali ni horbo into stick snacks, offering a modern variation that retains its cultural essence and health benefits while enhancing marketability. Conducted in Toba Regency from July to November 2024, this research involved 20 micro, small, and medium-sized enterprises (MSMEs) engaged in culinary entrepreneurship. A mixed-method approach was utilized, encompassing interviews to gather perceptions of dali ni horbo organoleptic properties and innovation potential, alongside sensory evaluation to assess attributes including color, texture, and taste. The results indicate high acceptance of the new product, with texture (mean score: 4.15) and taste (3.95) identified as strengths. However, improvements are necessary in aroma freshness and saltiness to align with broader consumer preferences. The study highlights Dali Ni Horbo's potential as a nutritious snack, leveraging its high protein and calcium content to address nutritional deficiencies. Moreover, this innovation supports local economic empowerment by creating opportunities for MSMEs and fostering sustainable practices in buffalo milk processing. In conclusion, transforming dali ni horbo into stick snacks bridges traditional culinary heritage and modern innovation, offering economic, cultural, and nutritional benefits. Recommendations include optimizing flavor profiles, diversifying products, and enhancing market access through strategic partnerships with government and private sectors to scale production and expand distribution. Keywords: Buffalo Milk, Cultural Innovation, Dali Ni Horbo, Sensory Evaluation.